Abnormal blood glucose concentrations on admission to a rural Kenyan district hospital: prevalence and outcome. - Osier, F; Berkley, J; Ross, A; Sanderson, F; Mohammed, S; Newton, C (2003)
AIMS: To determine the prevalence, clinical characteristics, and outcome of hypoglycaemia on admission in children at a rural Kenyan district hospital. METHODS: Observational study of 3742 children (including 280 neonates) in Kilifi District Hospital, Kenya. MAIN OUTCOME MEASURES: hypoglycaemia (blood glucose <2.2 mmol/l) and hyperglycaemia (blood glucose >10.0 mmol/l). RESULTS: Non-neonates: the prevalence of hypoglycaemia on admission was 7.3%. Severe illness, malnutrition, last meal >12 hours ago, and a positive malaria slide were independently associated with hypoglycaemia. Overall, mortality in hypoglycaemic children was 20.2% compared to 3.8% in normoglycaemic children (p < 0.001). The brunt of mortality in hypoglycaemic children was borne by those who were severely ill or malnourished (31.8%) as opposed to those who were neither severely ill nor malnourished (9.0%). Neonates: 23.0% of neonates were hypoglycaemic on admission. Inability to breast feed and weight <2500 g were independently associated with hypoglycaemia. Mortality was 45.2% compared to 19.6% in normoglycaemic neonates (p < 0.001). Hyperglycaemia was present in 2.7% of children and was associated with a higher mortality than normoglycaemia, 14.0% versus 3.8% respectively (p < 0.001). CONCLUSIONS: Hypoglycaemia is common in children admitted to a rural Kenyan district hospital and is associated with an increased mortality. Apart from features of severe illness and poor feeding, clinical signs have a low sensitivity and specificity for hypoglycaemia. Where diagnostic facilities are lacking, presumptive treatment of severely ill children is recommended. For other children, the continuation of feeding (by nasogastric tube if necessary) should be part of standard management.